THE INFLUENCE OF SMARTPHONE ADDICTION ON ONLINE COMPULSIVE BUYING WITH MOOD REGULATION AND FLOW EXPERIENCES AS MEDIATING VARIABLES - Maydirmasyah, Yoga; Afwa, Awliya; Moniko, Moniko (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study aims to examine and analyze the influence of smartphone addiction on online compulsive buying, as well as examining how mood regulation and flow experience mediate the influence of smartphone addiction on online compulsive buying in Generation Z in Riau Province. This research uses a quantitative approach with the Structural Equation Model analysis tool using SEM-PLS. The sampling technique in the research used G*power. This research tested 354 students as representatives of generation Z in Riau province with the finding that smartphone addiction had a direct influence on online compulsive buying, mood regulation and flow experience. Mood regulation has a direct effect on flow experience. flow experience has a direct influence on online compulsive buying. Smartphone addiction affects flow experience through mood regulation. Smartphone addiction influences online compulsive buying through flow experience. Smartphone addiction influences online compulsive buying through mood regulation and flow experience simultaneously. On the other hand, the findings of this study show that mood regulation has no effect on online compulsive buying. Mood regulation cannot act as a mediator in the influence of smartphone addiction on online compulsive buying.Keywords: smartphone addiction, mood regulation, flow experience, online compulsive buying